The Determinants of Capital Structure-The Comparison/Evidence in China - Wu, Dan (2011)
Capital structure theory has been broadly discussed and studied once it is raised by Modigliani and Miller in 1958. This paper attempts to investigate the determinants of capital structure of Chinese listed companies to compare with western countries. China is one of the rapidly emerging markets in the world, while its market environment varies; research results obtained in western countries are not entirely applicable to China’s situation. Among multiple angles economists have studied in, they always highlight the corporate capital structure as a unique spot of research interests. This paper examines the contemporary theories that capital structure involved in, as the trade-off theory and Pecking-order hypothesis, agency costs model and control theory. Moreover, the specific Chinese institutional environment also leads to the difference. After then, this paper examines and constructs empirical investigation to the determinants of capital structure in various companies. Additionally, the differences results between Chinese listed companies with western countries since internal and external influence factors will be discussed as well. Five years data of one hundred cross-sectional of non-financial listed companies in China are adopted in this paper, and panel data is applied to investigate the effect of institutional factors on the choice of capital structure with related variables being controlled. Due to the empirical results, profitability, firm size and tangibility are all positively correlated to total leverage, and statistically significant in this study. Only firm size is positively related to long-term leverage and statistically significant. In the last chapter, this paper put forward some policy recommendations for optimizing capital structure of listed companies and further research prospect.